Conserving indigenous cattle breeds can benefit Ethiopian smallholders - Philipsson, J. (International Livestock Research Institute, 2011)
On 15 and 16 November 2011, the International Livestock Research Institute (ILRI), Ethiopian Institute of Agricultural Research (EIAR), and the Swedish University of Agricultural Sciences (SLU) held a workshop on Sharing Research Results on Trypanotolerance in Indigenous Cattle Breeds and Experiences of Community Based Breed Improvement of Indigenous Sheep in Ethiopia. Here, Professor Jan Philipsson from the Swedish University of Agricultural Sciences explains how some breeds - such as the Sheko - are Trypanotolerant AND endangered. Thus it is important to exploit such breeds by conserving them, and multiplying them for long term use to benefit smallholders in Ethiopia.